Interleukin-12p70 Expression by Dendritic Cells of HIV-1-Infected Patients Fails to Stimulate gag-Specific Immune Responses. (12th July 2012) - Van Gulck, Ellen; Cools, Nathalie; Atkinson, Derek; Bracke, Lotte; Vereecken, Katleen; Vekemans, Marc; Van Tendeloo, Viggo F. I.; Berneman, Zwi N.; Vanham, Guido
Abstract : A variety of immune-based therapies has been developed in order to boost or induce protective CD8 + T cell responses in order to control HIV replication. Since dendritic cells (DCs) are professional antigen-presenting cells (APCs) with the unique capability to stimulate naïve T cells into effector T cells, their use for the induction of HIV-specific immune responses has been studied intensively. In the present study we investigated whether modulation of the activation state of DCs electroporated with consensus codon-optimized HxB2 gag mRNA enhances their capacity to induce HIV gag -specific T cell responses. To this end, mature DCs were (i) co-electroporated with mRNA encoding interleukin (IL)-12p70 mRNA, or (ii) activated with a cytokine cocktail consisting of R848 and interferon (IFN)- γ . Our results confirm the ability of HxB2 gag -expressing DCs to expand functional HIV-specific CD8 + T cells. However, although most of the patients had detectable gag -specific CD8 + T cell responses, no significant differences in the level of expansion of functional CD8 + T cells could be demonstrated when comparing conventional or immune-modulated DCs expressing IL-12p70. This result which goes against expectation may lead to a re-evaluation of the need for IL-12 expression by DCs in order to improve T-cell responses in HIV-1-infected individuals.